Contractual terms in musharakah and mudarabah restricting the profit share of a partner or facilitating later amendments to the agreed ratio: a scrutiny - Sadique, Muhammad Abdurrahman (International Islamic University Malaysia, 2013)
Equity participation in joint ventures as envisaged in Shari‘ah consists of a business relationship based on mutual sharing of gains and liability. Such partnerships as prevalent in every sphere of commerce generally involve the possibility of unlimited gains for each partner in theory, without limitations attached to the amount of return to any single partner. A central pillar of the equity structure in Shari‘ah is the unbridled operation of the profit sharing ratio. Restriction of its application to a stipulated level of profits, thereby enabling a partner to claim unlimited profits while the profit share of the other is restricted to a maximum ceiling cannot be regarded to be consistent with the theory of equity participation. While such measures could realise some temporary benefit to Islamic banks, with continued practice, they could become deep-rooted in the concept of equity financing itself, thus making it operate subservient to debt financing norms. Islamic banks should attempt to alienate their identity from being lending institutions, a pioneer step towards which would be to implement a dynamic profit and loss sharing mechanism.